Ionic Conductivity in the Metal–Organic Framework UiO‐66 by Dehydration and Insertion of Lithium tert‐Butoxide. Issue 18 (12th March 2013) - Ameloot, Rob; Aubrey, Michael; Wiers, Brian M.; Gómora‐Figueroa, Ana P.; Patel, Shrayesh N.; Balsara, Nitash P.; Long, Jeffrey R.
<x xml:space="preserve">Abstract</x> Shields up! Post‐synthetic modification of the secondary building units in the metal–organic framework UiO‐66 (Zr6O4(OH)4(O2CR)12) by dehydration and subsequent grafting of LiOtBu (see picture, green) yields a solid Li+ electrolyte with a conductivity of 1.8×10−5 S cm−1 at 293 K. As the grafting leads to screening of the anionic charge, the activation energy for ionic conduction is significantly lower than when Li+ is introduced through deprotonation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>